Issues in the Design and Validation of Coupled Reverberation Rooms for Testing Acoustic Insulation of Building Partitions - SZELĄG, Agata; ZASTAWNIK, Marcin (Archives of Acoustics, 2025)
The paper presents the characteristics of the sound field in two pairs of coupled reverberation rooms, designed in accordance with International Organization for Standardization [ISO] (2021c). The analyses are based on the results of the following studies. Firstly, the acoustic airborne sound insulation of selected test samples was measured in the reverberation rooms without using any sound diffusing nor sound absorbing elements. In the second step, the tests were repeated successively with an increasing number of diffusers installed in the rooms. The last stage of the research involved measurements with additional absorbers mounted in the rooms. The results show that although the geometry and construction of the reverberation rooms are in line with the standard guidelines, in most situations it was necessary to use diffusing and absorbing elements to improve the acoustic field in the rooms. Such elements, however, are very undesirable as they significantly limit the usable space of the rooms, making it more difficult to assemble samples and distribute sources and measurement points in the measurement space. Later in the article, the authors prove that even using typically available design tools, i.e., 1st and 2nd Bonello criterions, numerical simulations with the image-source method and the finite element method, or more advanced research methods, such as measurements using scaled samples, it seems impossible to prevent at the design stage the future necessity of using additional diffusing and absorbing elements in the reverberation rooms. Only via verification by measurements performed in the completed rooms provides the assessment if such additional elements are required.